Hedging Effectiveness of Index Futures against Exchange Traded Fund - Ming Fang , Chiu -Lan Chang, Aubery Xuewei Chen , (Design Engineering, 2020)
A common quantitative trading technique involves two types of assets to construct hedging portfolio, such using futures with ETFs as a hedge portfolio.The hedging effectiveness(HE) of SSE 50 index futures(FSSE) become to a brand-new issue in response to being launched in 2015. This study aims to examine the HE of FSSE and SSE 50 Exchange Traded Fund (ETFSSE) applied with several hedging models including the ordinary least squares model (OLS), Bayesian Vector Autoregressive model (BVAR), GARCH model (GARCH) and BEKK-GARCH model (BEKK). These models are applied to estimate the optimal hedge ratios (H*) and HE. The empirical results reveal that all models present good hedge performance than naïve hedge, and the HE of GARCH is the highest. The findings enable investors to get more informed and practical suggestions about investment decision-making in risk management.